Exploring intercultural dialogic interactions between individuals with diverse feedback literacies. Issue 7 (3rd October 2022) - Rovagnati, Veronica; Pitt, Edd
Abstract: Feedback is a dialogic process in which diverse individuals are involved. In internationalised higher education, individuals with different feedback literacies are likely to participate in feedback dialogues and interactions across feedback cultures. Such intercultural interactions can be challenging; some degree of intercultural competence is needed for dialogues between cultures to be effective and appropriate for all involved. This paper brings together feedback and intercultural competence research, exploring whether developing intercultural competence specific to feedback contexts can support more effective dialogues. Narrative interviews and audio diary methods were employed over a 9-month period of time to explore the role of intercultural competence in feedback dialogues across feedback cultures. Changes over time were captured through the longitudinal design of the study. Findings show that knowledge and awareness of diverse feedback practices and cultures, intercultural critical reflection, intercultural emotional management, alongside a set of skills and attitudes towards diversity of feedback practices can impact on facilitating intercultural feedback dialogues. A framework of feedback intercultural competence is proposed, and further research is encouraged to expand upon this exploratory papers' initial contribution.